Work Design and Personality with Their Influence on Improving Employee Performance with a Congruence Theory Perspective - Garibaldi, Ganjar (Clean and Sustainable Production, 2024)
The research to be conducted is to examine the performance of organizational human resources, which are influenced by Work Design using the job characteristics model (JCM) and Personality using the Big five model (Big Five), as well as by using the perspective of Congruency Theory. This research is based on the issue of economic recovery after the COVID pandemic from a management perspective. The object of research is 53 State Civil Apparatus. at the Regional Business Management & Investment Unit (PUDPM) in West Java. An organization that functions in economic recovery through the arrangement of existing businesses, as well as management related to investment in regional areas in West Java province, post-pandemic COVID. The research methods used is a verificative qualitative method, with data collection techniques using questionnaires. The tests used for instrument testing are validity tests and reliability tests. In data analysis, multiple linear regression analysis is used, correlation coefficient analysis and determination and hypothesis testing using T test (partial) and F test (simultaneous). The results of the correlation coefficient analysis show that 68% of employee performance is influenced by personality and work design, while the rest is influenced by other variables. While the results of the coefficient of determination were 46.2% and the rest were influenced by other variables that were not studied by researchers.